Living Quran Study (a New Approach in the Development of Quranic Tafsir) - Muhammad Esa Prasastia A (Green Publisher Indonesia, 2021)
This study aims to describe the meaning of the living Quranand understand how the history of the emergence of livingQuran studies in society and the advantages anddisadvantages of living Quran studies. This study uses alibrary research method that refers to available sourcesboth online and offline such as: scientific journals, booksand news sourced from sources Trusted. This data wasobtained through triangulation techniques. The data wereanalyzed and then conclusions were drawn. The results ofthis study are this kind of study will be more appreciative ofthe response and behavior of the community towards thepresence of the Qur'an, so that the interpretation is nolonger only elitist, but emancipatory that invites publicparticipation. The phenomenological, sociological,anthropological and analytical approaches of the socialhumanities sciences as well as several other disciplines, ofcourse, are very supportive factors in this study.Furthermore, the Living Quran can also be used for thebenefit of da'wah and community empowerment, so thatthey are more optimal in appreciating the Koran.